2019
DOI: 10.1103/physrevd.100.074001
|View full text |Cite
|
Sign up to set email alerts
|

Radiative decays in bottomonium beyond the long wavelength approximation

Abstract: We revisit the nonrelativistic quark model description of electromagnetic radiative decays in bottomonium. We show that even for the simplest spectroscopic quark model the calculated widths can be in good agreement with data once the experimental masses of bottomonium states and the photon energy are properly implemented in the calculation. For transitions involving the lower lying spectral states this implementation can be easily done via the Long Wave Length approximation. For transitions where this approxim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 20 publications
2
20
2
Order By: Relevance
“…In a recent paper [3], we have shown that this discrimination may be rather difficult in bottomonium. By using the standard expansion of the electromagnetic transition operator up to p b =M b order, where p b ðM b Þ stands for threemomentum (mass) of the b quark, we have shown that accurate results for the widths can be obtained from different quark potential models reasonably fitting the spectroscopy once the experimental masses of the bottomonium states instead of the calculated ones are properly implemented in the calculation.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In a recent paper [3], we have shown that this discrimination may be rather difficult in bottomonium. By using the standard expansion of the electromagnetic transition operator up to p b =M b order, where p b ðM b Þ stands for threemomentum (mass) of the b quark, we have shown that accurate results for the widths can be obtained from different quark potential models reasonably fitting the spectroscopy once the experimental masses of the bottomonium states instead of the calculated ones are properly implemented in the calculation.…”
Section: Introductionmentioning
confidence: 85%
“…It is important to emphasize that (i) this potential form arises from spin independent quenched lattice QCD calculations in the Born-Oppenheimer approximation [4], (ii) in the spirit of the nonrelativistic quark model calculations σ, ζ, β and the quark mass M c should be considered as effective parameters through which spin dependent and/or spin independent corrections may be implicitly incorporated. Henceforth we shall make use of two different quark models with the same Hamiltonian form (1), Model I and Model II, that have been used for the analysis of radiative decays in bottomonium [3]. As we are dealing with a radial potential we shall denote the spectroscopic states by n 2sþ1 L J where s, L, and J stand for the spin, orbital angular momentum, and total angular momentum quantum numbers respectively.…”
Section: Spectroscopic Quark Modelsmentioning
confidence: 99%
See 3 more Smart Citations